Thermoelectric and mechanical properties of Ag and Cu doped (GeTe)0.96(Bi2Te3)0.04. (8th August 2018) - Guttmann, Gilad M.; Gertner, Reuven; Samuha, Shmuel; Ben-Ayoun, Dana; Haroush, Shlomo; Gelbstein, Yaniv
Abstract: Abstract : Thermoelectric (TE) is a heat-to-electricity energy conversion method with increasing attention. In recent years, novel highly efficient TE materials, including GeTe and other IV–VI based alloys, were reported, mainly due to either electronic optimization of transport properties or nanostructuring for minimization of the lattice thermal conductivity. Yet, the mechanical properties of such materials (with brittle nature), which are significant for obtaining the required durability under the associated thermo-mechanical conditions of practical applications, were much less tackled. The challenge is combining the both, upon introducing alloying elements, positively contributing both the TE figure of merit and the mechanical durability. In the current research, the TE and mechanical (mainly compression and fracture toughness) effects of Ag- and Cu-doping of the GeTe-rich (GeTe)0.96 (Bi2 Te3 )0.04 alloy were investigated, suggesting improvement on both aspects.